ON SECURE FULL DUPLEX COMMUNICATION IN MOBILE AD HOC NETWORK - S. C. Dutta; Sudha Singh; D. K. Singh (ICTACT Journal on Communication Technology, 2013)
This paper is to establish Ad Hoc network in mobile phones and start fully secured full duplex communication in any situation. This type of communication will be cost effective and it will be fastest way of communication in case of any server failure or server error.